Reading the Song of Songs through a spiritual direction lens - Lam, Judy E. (HTS teologiese studies, 2015)
Research on the use of the Song of Songs in spiritual direction is rare; yet, the Song of Songs (or Canticle of Canticles) is a highly conducive case as it provides in nuce the poetics, lyrics, erotics, and aesthetics of human and divine love which is found nowhere else in Scripture. This article draws on these unique features, integrates the biblical and the experiential, and offers a poetics-praxis paradigm for use in contemporary spiritual praxis. With the poem’s metaphorical vineyard (a figurative term for the beloved herself) serving as hermeneutical key, the beloved’s experience of love is interpreted through a multifaceted reading that is intrinsic to the poem, namely: eros [yearning]; mythos [searching]; mustikos [finding]; and kosmos [birthing]. In following the inner dynamism and dramatic tensions across the eight chapters of the Song, the fourfold reading traces the beloved’s transformation from a neglected vineyard (Can 1:6) to a generative vineyard (Can 8:12). The article concludes that transformation in love is a journey from depletion (the giving away of self) towards deification (the giving of self in love), and suggests tending one’s own vineyard as a living testament to divine love and a living sacrament in the world.